Athletic Conference Consideration for Adding New Sports Post-COVID - Milstein, Sloane; Lanzillo, Julie; Damon, Zack (Journal of Intercollegiate Sport, 2023)
COVID-19 has impacted the sport industry across all contexts, including intercollegiate athletics. Specifically, research has found that the Collegiate Sport Addition Process (CSAP) to add or remove a sport for athletic departments in previous economic downturns must consider multiple factors. The current study builds on previous research by exploring the considerations of adding a sport through a buyer-seller interaction framework. Specifically, the current study explored whether sport governing bodies or coaching associations should attempt to sell their sport at the intercollegiate Conference level, rather than at the institution level. The current study used a survey to collect feedback from conference commissioners across the intercollegiate sport landscape. Through surveys and follow-up interviews, findings led to emergent themes of balance, viability, funding and revenue, and post-season opportunities as factors that conference personnel considered when deciding to add a sport. Theoretical and practical implications are discussed.